PERAN ETIKA WANITA JAWA DALAM BERUMAH TANGGA (KAJIAN TERHADAP SERAT CENTHINI) - Roro Ajeng Apriyana Roro Ajeng Apriyana (Program Studi Pendidikan Sejarah - Universitas Samudra, 2023)
Serat Centhini or Suluk Tambangraras, is a complete encyclopedia of the world in Javanese society. Javanese women are women who were raised with Javanese values. Javanese women are also known as women who are smooth, calm, calm, and should not exceed men. Therefore, Javanese women must be able to accept everything that has become their nature. This study aims to examine the ethics of Javanese women in the household and examine the relevance of Serat Centhini to the ethics of Javanese women in the household. The method used is the Historical method, so the steps used in this study include heuristics, source criticism, interpretation and historiography. Based on the results of the study, it was concluded that the ethics of Javanese women in the household stated that the ethics of Javanese women could be divided into spirituality, sociality and personality. In the spiritual realm, Serat Centhini teaches women's relationship with God as a religious teaching. In the field of sociality, teaching women about relationships with the community. Finally, women must comply with ethical norms, such as ethics towards parents, family, and society. Along with the changing times, the ethical relevance of Javanese women then and now has undergone a significant change. The current woman, can be said to have been very advanced. This is due to the culturalization of culture, which resulted in many people abandoning the old teachings. The noble values ​​in Serat Centhini are now a mirror of life for the community. In addition to adding knowledge, it is also a lesson for Javanese women's behavior that deserves to be an example for women today.